Effect of riociguat on right ventricular function in patients with pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension - Benza, Raymond L; Ghofrani, Hossein-Ardeschir; Grünig, Ekkehard; Hoeper, Marius M; Jansa, Pavel; Jing, Zhi-Cheng; Kim, Nick H; Langleben, David; Simonneau, Gérald; Wang, Chen; Busse, Dennis; Meier, Christian; et al. (The Journal of heart and lung transplantation, 2021)
BACKGROUND: In the Phase III PATENT-1 (NCT00810693) and CHEST-1 (NCT00855465) studies, riociguat demonstrated efficacy vs placebo in patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). Clinical effects were maintained at 2 years in the long-term extension studies PATENT-2 (NCT00863681) and CHEST-2 (NCT00910429). METHODS: This post hoc analysis of hemodynamic data from PATENT-1 and CHEST-1 assessed whether riociguat improved right ventricular (RV) function parameters including stroke volume index (SVI), stroke volume, RV work index, and cardiac efficiency. REVEAL Risk Score (RRS) was calculated for patients stratified by SVI and right atrial pressure (RAP) at baseline and follow-up. The association between RV function parameters and SVI and RAP stratification with long-term outcomes was assessed. RESULTS: In PATENT-1 (n = 341) and CHEST-1 (n = 238), riociguat improved RV function parameters vs placebo (p < 0.05). At follow-up, there were significant differences in RRS between patients with favorable and unfavorable SVI and RAP, irrespective of treatment arm (p < 0.0001). Multiple RV function parameters at baseline and follow-up were associated with survival and clinical worsening-free survival (CWFS) in PATENT-2 (n = 396; p < 0.05) and CHEST-2 (n = 237). In PATENT-2, favorable SVI and RAP at follow-up only was associated with survival and CWFS (p < 0.05), while in CHEST-2, favorable SVI and RAP at baseline and follow-up were associated with survival and CWFS (p < 0.05). CONCLUSION: This post hoc analysis of PATENT and CHEST suggests that riociguat improves RV function in patients with PAH and CTEPH.
Keywords: Stroke Volume; Pulmonary Embolism; síňový tlak; aktivátory enzymů; výsledek terapie; Atrial Pressure; plicní embolie; Hypertension, Pulmonary; Middle Aged; mužské pohlaví; Ventricular Function, Right; Adult; funkce pravé komory srdeční; Pyrimidines; pyrimidiny; Follow-Up Studies; tepový objem; Enzyme Activators; následné studie; Pyrazoles; ženské pohlaví; plicní hypertenze; Humans; lidé středního věku; pyrazoly; dospělí; Female; Treatment Outcome; lidé; Male